1992
DOI: 10.1007/bf00002936
|View full text |Cite
|
Sign up to set email alerts
|

A global budget for atmospheric NH3

Abstract: Abstract. We provide an assessment of the global sources of NH, in the atmosphere, which indicates an annual flux of about 75 Tg of N as NH,. The emissions from land are dominated by the release of NH, during the hydrolysis of urea from the urine of domestic animals (32 TgN/yr) and by emanations from soils in unmanaged' ecosystems (10 TgN/yr) and from fertilized agricultural soils (9 TgN/yr). Emissions from the sea surface may approach 13 TgN/yr. The total annual source of NH, is in reasonable agreement with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
161
2
6

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(176 citation statements)
references
References 99 publications
7
161
2
6
Order By: Relevance
“…By comparing with other studies cited here, Kent seems to fall into the range of a typical rural region, with regard to the ambient [NH 3 ] level. For example, [NH 3 ] in the remote marine atmosphere were 86 pptv on average (Schlesinger and Hartley, 1992) and as low as 20 pptv in some remote areas (Dentener and Crutzen, 1994). Rural regions in the eastern United States have shown [NH 3 ] of 100-500 pptv (Dentener and Crutzen, 1994) with a mean [NH 3 ] of 300 pptv (Langford et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By comparing with other studies cited here, Kent seems to fall into the range of a typical rural region, with regard to the ambient [NH 3 ] level. For example, [NH 3 ] in the remote marine atmosphere were 86 pptv on average (Schlesinger and Hartley, 1992) and as low as 20 pptv in some remote areas (Dentener and Crutzen, 1994). Rural regions in the eastern United States have shown [NH 3 ] of 100-500 pptv (Dentener and Crutzen, 1994) with a mean [NH 3 ] of 300 pptv (Langford et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Rural regions in the eastern United States have shown [NH 3 ] of 100-500 pptv (Dentener and Crutzen, 1994) with a mean [NH 3 ] of 300 pptv (Langford et al, 1992). Global NH 3 emission data taken with infrared satellite observations show that concentrations in the eastern United States are low and no significant hotspots exist in this region (Clarisse et al, 2009 (Dentener and Crutzen, 1994) and [NH 3 ] up to 430 ppbv have been seen in strong point source locations (Schlesinger and Hartley, 1992). Emission measurements made in different automobile tunnels have shown [NH 3 ] of 50-400 ppbv (Fraser and Cass, 1998;Kean et al, 2000;Moeckli et al, 2004) [NH 3 ] of 20-70 ppbv have also been reported from smoke (Yokelson et al, 1999Goode et al, 2000), as well as 100-200 ppbv in biomass burning plumes (Hurst et al, 1994;Li et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For China, we use,:t a range of emission factors because of the differences in animal husbandry. To calculate Chinese minima and maxima animal emission factors, w~ used the Dentener and Crutzen (1994) values, reduced by 40% to account for the dispersive nature of animal husbandry practices in less-developed countries (Dentener and Crutzen, 1994), together with the Schlesinger and Hartley (1992) and the Zhao and Wang (1994) values (Table 4). We did not consider Battye et al (1994) because their values are based specifically on the 1991 animal population structures of animals in the United States (Table 4) …”
Section: Nr Emissionmentioning
confidence: 99%
“…The spatial differences of SO 2 and NH 3 concentrations between the two sites might be due to their different emission sources. SO 2 comes primarily from fossil fuel burning activities (e.g., coal consumption), while NH 3 comes generally from agricultural activities (Schlesinger and Hartley, 1992;Zhao and Wang, 1994;ECETOC, 1994;Bouwman et al, 1997). No evident correlation between SO 2 and NH 3 concentrations in the air at the two sampling sites (Fig.…”
Section: Monitoring Data and Correlation Analysismentioning
confidence: 93%